Reproduction biology of Abe's flyingfish, Cheilopogon abei Parin, 1996 in Geser East Seram Strait Waters - Friesland Tuapetel (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2021)
Eco-biological information of Cheilopogon abei in Geser Streit is unknown. The objective of this research is to observe the sex ratio, first size maturity, gonad maturity and gonado somatic index (GSI) with fecundity of flying fish Ch abei in Geser East Seram Strait waters. Sampling was done for ten months started from February to November 2018, using gill net measuring 1.50 inch. All fish samples were measured in fork length and weighted so dissected to make observations on the level of gonad maturity and the number of eggs in female fish. A total of 682 flying fish was found during the study with a fork length range of 182.6-243.3 mm and a weight of 73.98-115.45 g. The results of the analysis showed that the proportion of the number of male fish was less than that of the female fish for almost every month of observation. The first size gonad mature of male and female is 210.5 mm and 214.1 mm FL. The gonad maturity index of male fish ranges from 0,963-7,967 and female fish ranges 1,315-8,069, the total fecundity is 2321-9438 eggs. Gonads of ripe fish in each month of observation. The spawning peak of Ch abei takes place in June-July and it is hoped that no arrests will be made in both months, to ensure the sustainability of the stock. Abstrak Informasi ekobiologi ikan terbang Cheilopogon abei di peraian Selat Geser belum pernah ada. Penelitian ini bertujuan untuk mengungkap nisbah kelamin, ukuran ikan pertama mijah, tingkat dan indeks kematangan gonad serta fekunditas ikan terbang di Selat Geser Seram Timur. Pengambilan sampel dilakukan selama sepuluh bulan mulai Februari sampai Nopember 2018, dengan menggunakan jaring insang berukuran 1,50 inci. Semua contoh ikan diukur panjang serta ditimbang bobotnya lalu dibedah untuk melakukan pengamatan terhadap tingkat kematangan gonad serta jumlah telur pada ikan betina. Sebanyak 682 ikan terbang ditemukan selama penelitian dengan kisaran panjang cagak 182,6-243,3 mm dan bobot 73,98-115,45 g. Hasil analisis menunjukkan bahwa proporsi jumlah ikan jantan lebih sedikit daripada ikan betina hampir pada setiap bulan pengamatan. Ukuran kali pertama matang gonad ikan jantan dan betina ialah 210,5 mm dan 214,1 mm FL. Indeks kematangan gonad ikan jantan berkisar antara 0.963–7,967 dan ikan betina antara 1,315–8,069, fekunditas totalnya yakni 2321-9438 butir. Ikan yang matang gonad ditemukan pada setiap bulan pengamatan. Puncak pemijahan C. abei berlangsung pada bulan Juni-Juli dan diharapkan tidak ada penangkapan pada kedua bulan tersebut, untuk menjamin keberlanjutan stoknya.